Placental thickness in third trimester and its correlation to gestational age and fetal weight in primigravida - Badu, Muna; Singh Rajbhandari, Shankar Bahadur; Regmi, Pashupati (Journal of Kathmandu Medical College, 2020)
Background: Gestational age and fetal weight estimation by ultrasound is the most effective and accurate method to date pregnancy. Ultrasound has been used to characterize placental position and morphologic changes. Placental thickness could be one additional parameter to assess gestational age and fetal weight. Objectives: This study aims to investigate the relationship between placental thickness with gestational age and fetal weight in third trimester of pregnancy in primigravida. Methodology: Prospective hospital based cross sectional study was conducted including 111 primigravida in third trimester with normal singleton pregnancies in Department of Radiology of Kathmandu Medical College Teaching Hospital from November 2018 to February 2019. Patients with known medical and obstetrical complications were excluded from the study. Placental thickness in millimeters was measured at the level of insertion of the umbilical cord. Pearson’s correlation analysis was used for analyzing variables and p-value <0.05 was considered statistically significant. Results: Mean age of participants was 28.3 ± 4.79 years. Posterior location of the placenta was most common (35%). Placental thickness correlated well with the gestational age and fetal weight. Pearson correlation coefficient was found to be 0.645 for placental thickness with gestational age and 0.598 for placental thickness with fetal weight. P-value was <0.001 in both, showing positive correlation of mentioned variables with placental thickness. Conclusion: Placental thickness can be a new and reliable parameter for estimation of gestational age and fetal weight. It can be routinely used during antenatal checkup.